Carbon markets, energy transition, and green development: a moderated dual-mediation model - Kong, Shaohua; Li, Hanzun; Tan, Shuwen (Frontiers in Environmental Science, 2023)
Introduction: Carbon market is an important market instrument to deal with environmental problems and an important practice of the green development concept. Among the many economic sectors in China, the energy sector is the largest emitter of carbon dioxide, therefore, the transformation of the energy sector is the focus of China's green development. Methods: This study used data from 211 prefecture-level cities in China from 2015 to 2020 to construct carbon market, green development, energy transition (shift to clean and low-carbon energy), and financial development indices to determine how to achieve green development beginning with a carbon emissions market and investigate how carbon markets affect environmentally friendly development from a green economics perspective. Unlike previous studies, this study uses a moderated dual mediation model for analysis to examine the indirect impact of carbon markets on green development through energy efficiency and new energy use channels of energy transition. Afterward, examine how financial development influences carbon markets and green development and the mediating effect of such development in eastern, central, and western China are performed, respectively. Results: The empirical results of this study reveal the following: first, carbon markets directly influence green development in a favorable way. Second, energy transition creates a bridge between carbon markets as well as green development; and third, financial development plays a moderating role among carbon markets, energy transition, and green development. Discussion: Based on the empirical findings, this study provides recommendations for promoting green development, such as enhancing information disclosure and guiding green finance development.